PENGARUH KAPUR SEBAGAI STABILIZING AGENT TERHADAP INDEKS PLASTISITAS DAN KUAT GESER LEMPUNG EKSPANSIF MEUNASAH RAYEUK - Teuku Julis Syamdiofa; Munirwansyah Munirwansyah; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2018)
Clay soil from Desa Meunasah Rayeuk quarry in Kaway XVI, West Aceh Regency is a land material frequently used for construction of road infrastructure. In this quarry, there are three types of soil based on the color, yellow, red, and gray. The three types of soil have expansive characteristics, so they are not suitable for subgrade. This unoptimal characteristic can be improved through soil stabilization. One of them by utilizing the reaction of catinonization between lime Ca(OH)2 with the clay soil. Therefore, a research needs to be conducted to find out the characteristics of physical and mechanical properties of the original soil and the effect of cationization of the soil and lime mixture on the soil plasticity index and soil shear strength parameters. Testing is done through mineralogical test and ASTM standard tests that include physical properties, standard compaction, and direct shear strength test. Variations of lime addition are 0%, 3%, 6%, 9%, and 12% of the soil dry weight. The test results show that the addition of lime can reduce the soil plasticity index and increase the shear strength of the soil on some level. At mixing up to 12% lime, the soil plasticity index dropped to 12.93% in yellow clay, 11.12% in red clay, and 16,76% in gray clay. The plasticity index after the addition of 12% lime has not met the minimum plasticity index requirement, ie 11%. The maximum shear strength for yellow clay is obtained at 3% lime, and 6% lime for red and gray clays.